Ticks : biology, ecology, and diseases - Johnson, Nicholas, 1968- (Elsevier, Academic Press, an Imprint of Elsevier, 2023)
Ticks: Biology, Ecology and Diseases provides a detailed overview of the fascinating world of tick biology and ecology. This book discusses disease transmission to humans and livestock, assesses the impact of human behavior and climate change on tick biology, and details how this will affect future disease transmission. Written by an expert on ticks and their transmitted diseases, this book explores the unique biology of ticks and how it influences the transmission of some of the most devastating diseases. In a series of detailed chapters, the book provides up-to-date information on the interrelationship between ticks and the vertebrates they feed on. In addition, the book covers information on recent scientific discoveries surrounding ticks, along with reviews on control methods and disease transmission. Other sections cover the recent emergence of tick-borne pathogens, making this book an ideal source for interested scientists, clinicians, veterinarians and experts in the field of tick biology.